Dietary Fatty Acids from Leaves of Clerodendrum Volubile Induce Cell Cycle Arrest, Downregulate Matrix Metalloproteinase-9 Expression, and Modulate Redox Status in Human Breast Cancer. (18th May 2016) - Erukainure, Ochuko L.; Zaruwa, Moses Z.; Choudhary, M. Iqbal; Naqvi, S. Asma; Ashraf, Nadia; Hafizur, Rahman M.; Muhammad, Aliyu; Ebuehi, Osaretin A.T.; Elemo, Gloria N.
ABSTRACT: The antiproliferative effect of the fatty acid components of Clerodendrum volubile leaves as well as its antioxidant effect on MCF-7 and MDA-MB-231 human breast cancer cell lines were investigated. Fatty acids extracted from C. volubile leaf oil were subjected to gas chromatography mass spectrometry (GCMS) analysis. The cells were cultured and treated with the fatty acids for 48 h, after which the antiproliferation effect was ascertained via MTT assay and cell viability analysis using BD fluorescence activated cells sorting (FACS) Calibur. Cell cycle was analyzed by flow cytometry on FACS Calibur. Western blotting was used in determining expression of proteins in the cell lines. The treated cell lines were assessed for reduced glutathione level, catalase, superoxide dismutase, and lipid peroxidation. The fatty acids significantly inhibited cell proliferation, arrested G0/G1 phase, downregulated the expression of MMP-9, and attenuated oxidative stress in of MCF-7 cell lines but had little or no effect on MDA-MB-231 cell lines. These results indicate the therapeutic potential of the fatty acids components of the leaves of C. volubile on human breast cancer, which may be explored further in drug development.